PELATIHAN FITUR OTOMATISASI DOKUMEN MICROSOFT WORD UNTUK MENINGKATKAN KETERAMPILAN PENYUSUNAN DOKUMEN AKADEMIK DI STMIK LOMBOK - Zulkipli; Amir Bagja; Zaenul Amri; M Nurul Wathani; Muhamad Rodi (LPPM STMIK Lombok, 2025)
This training activity aims to enhance participants' skills in utilizing Microsoft Word’s document automation features, including automatic table of contents creation, figure listing, page numbering, and cross-referencing. The training was conducted in the REC Room of STMIK Lombok on Wednesday, May 28, 2025, involving 40 participants. The method used was a hands-on approach (learning by doing), and participants were evaluated through pre-test and post-test assessments. The pre-test results showed that 17 participants were in the